‘One Chance in a Thousand’: The Mission of Sumner Welles to Europe (Feb-Mar 1940), Rooseveltian Foreign Policy and Anglo-American Relations Nov 1937- May 1940 - J. Simon Rofe (2005)
This work presents a new analysis of the mission undertaken by Under Secretary of State Sumner Welles to Europe on behalf of President Roosevelt in February-March 1940.The thesis asks what Roosevelt’s motivations were for undertaking the mission, and what he sought to achieve from it. It considers that the Welles mission was an expression of a number of influences upon Roosevelt that date back to late 1937. These influences, or themes, which provide the broader context and run throughout the period up to the beginning of 1940, are as follows: firstly the integral role in Rooseveltian foreign policy played by Sumner Welles is considered. The second theme concerns the position of his superior, Secretary of State Cordell Hull, who was to counsel caution in the face of an increasingly serious world situation, whilst a third influence was the limits upon American foreign policymaking itself. The last element to be considered throughout this study is the influence of Anglo- American relations upon the Welles mission. Further, these themes are not distinct and are interrelated. And all were subject to the influence of an American public who were deeply interested in, but firmly against intervention in, European affairs.This work concludes that the mission that resulted developed multiple objectives after being bom out of a discussion between Roosevelt and Welles on the role the United States could play in achieving a sound and lasting peace in Europe. Such a hope, reckoned by Roosevelt to be ‘one chance in a thousand’, was at the outset incongruous with the situation in Europe. Roosevelt and Welles knew this to be the case, and pressed ahead because of the existence of other objectives that such a mission could achieve. These were the gathering of first-hand information by Welles from the four capitals of Europe, the perpetuation of Italian neutrality and the prolonging of the ‘phony war’. These objectives were never clarified by the protagonists and evolved in themselves through the deployment of the mission, thus requiring the analysis provided here.